A review of human swarm interaction - Barca, Jan Carlo (IAES International Journal of Robotics and Automation (IJRA), 2026)
A review of recent activities in Human Swarm Interaction (HSI) research is presented in this paper. The paper begins with providing a short description of swarming. It then discusses HSI and explains why it is beneficial to enable human operators to supervise swarms of robots. Then, a wide range of papers, which present novel methods for interacting with swarms of robots, are reviewed. Four control methods that can be used to transmit an operator’s intent to a swarm are also discussed. Levels of autonomy and flexible autonomy in HSI are furthermore described. At the end of the paper, a discussion of the gaps in knowledge that still must be filled to enable swarms of robots to operate in the real world is presented. It is suggested that more research into techniques for remote interaction with robotic swarms be conducted. This includes methods that enable remote interaction with swarms of swarms. More work on HSI in degraded communications environments is also required. Additional research into swarm autonomy is furthermore needed to facilitate efficient supervisory control. Lastly, there is room for more work on trust in HSI, as robotic swarms can only be used by humans if they can be trusted.